2019
DOI: 10.1080/02656736.2019.1635718
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-endurance events in tropical environments and countermeasures to optimize performances and health

Abstract: Physical performance in a tropical environment, combining high heat and humidity, is a difficult physiological challenge that requires specific preparation. The elevated humidity of a tropical climate impairs the thermoregulatory mechanisms by limiting the rate of sweat evaporation. Hence, a proper management of whole-body temperature is required to complete an ultra-endurance event in such an environment. In these long-duration events, which can last from 8 to 20 h, held in hot and humid settings, performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 81 publications
0
4
0
4
Order By: Relevance
“…De nombreuses études ont tenté de vérifier s'il y avait un intérêt à recourir à des stratégies d'acclimatation, passive ou active, dans le cadre de la pratique sportive [13]. Il a ainsi été montré que l'acclimatation à une TE entraînait des adaptations physiologiques telles qu'une réduction de la consommation d'oxygène à une puissance donnée, une économie du glycogène musculaire, une réduction de lactate sanguin à une puissance donnée, une augmentation de la force produite, une augmentation de la sudation, une diminution de la concentration en sel de cette dernière, une augmentation du volume plasmatique et une amélioration de l'efficacité du myocarde [12,[38][39], tout en limitant les risques d'abandons [40] ainsi que les problèmes de santé liés à la chaleur [2]. Ces derniers ont ajouté que la répétition d'exercices en condition de TE favorisait l'acclimatation active des athlètes à la chaleur, via une série d'adaptations physiologiques (e.g., diminution de la fréquence cardiaque) améliorant la thermorégulation et réduisant les contraintes physiologiques (i.e., diminution de la température centrale) pour des exercices réalisés à une intensité donnée.…”
Section: Stratégies Usuelles De Gestion D'une Température Elevée Accl...unclassified
See 1 more Smart Citation
“…De nombreuses études ont tenté de vérifier s'il y avait un intérêt à recourir à des stratégies d'acclimatation, passive ou active, dans le cadre de la pratique sportive [13]. Il a ainsi été montré que l'acclimatation à une TE entraînait des adaptations physiologiques telles qu'une réduction de la consommation d'oxygène à une puissance donnée, une économie du glycogène musculaire, une réduction de lactate sanguin à une puissance donnée, une augmentation de la force produite, une augmentation de la sudation, une diminution de la concentration en sel de cette dernière, une augmentation du volume plasmatique et une amélioration de l'efficacité du myocarde [12,[38][39], tout en limitant les risques d'abandons [40] ainsi que les problèmes de santé liés à la chaleur [2]. Ces derniers ont ajouté que la répétition d'exercices en condition de TE favorisait l'acclimatation active des athlètes à la chaleur, via une série d'adaptations physiologiques (e.g., diminution de la fréquence cardiaque) améliorant la thermorégulation et réduisant les contraintes physiologiques (i.e., diminution de la température centrale) pour des exercices réalisés à une intensité donnée.…”
Section: Stratégies Usuelles De Gestion D'une Température Elevée Accl...unclassified
“…Selon [13], la plupart des adaptations physiologiques sont obtenues au bout de quelques jours en condition de TE. Cependant, la capacité à réaliser un exercice physique en condition de chaleur semble s'améliorer de façon optimale après une à deux semaines dans les conditions en question avec une pratique physique régulière, ce qui amène des auteurs (e.g., [13,40]) à suggérer d'être sur les lieux de compétitions au moins 14 jours avant le début des épreuves (voir Figure 1).…”
Section: Stratégies Usuelles De Gestion D'une Température Elevée Accl...unclassified
“…It is well known that environmental conditions such a wind and heat have an influence on ultra-endurance performance [62]. While it is known that wind has an influence on ultra-cycling performance [63], one might assume that also heat might impair ultra-endurance performance [64]. Triathletes competing under thermal stress conditions in the 'Ironman Hawaii' reached a state of hyperthermia during the marathon [65].It was observed that overall time was predictive for cycling performance of the following day and sleep time was not related to performance.…”
Section: Energy Expenditure Loss In Body Mass and Body Weight As Prementioning
confidence: 99%
“…A hot and humid climate (HHC), associated with a relatively high temperature and high humidity and commonly associated with a tropical climate, is known to significantly decrease the body’s capacity to eliminate the heat produced by cell metabolism. The high relative humidity (RH) of the HHC prevents the evaporation of sweat, neutralizing its exothermic capacity, and the relatively high temperature considerably reduces the body’s thermal losses by conduction, convection and radiation [ 1 ]. Practicing activity/exercise in a HHC induces a performance decrease associated with a higher risk of casualties, such as heat stroke, injury, dehydration, or hyponatremia [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%